Induction of the type I interferon response in neurological forms of Gaucher disease. Issue 1 (December 2016) - Vitner, Einat; Farfel-Becker, Tamar; Ferreira, Natalia; Leshkowitz, Dena; Sharma, Piyush; Lang, Karl; Futerman, Anthony
Abstract Background Neuroinflammation is a key phenomenon in the pathogenesis of many neurodegenerative diseases. Understanding the mechanisms by which brain inflammation is engaged and delineating the key players in the immune response and their contribution to brain pathology is of great importance for the identification of novel therapeutic targets for these devastating diseases. Gaucher disease, the most common lysosomal storage disease, is caused by mutations in theGBA1 gene and is a significant risk factor for Parkinson's disease; in some forms of Gaucher disease, neuroinflammation is observed. Methods An unbiased gene profile analysis was performed on a severely affected brain area of a neurological form of a Gaucher disease mouse at a pre-symptomatic stage; the mouse used for this study, theGba flox/flox ; nestin-Cre mouse, was engineered such thatGBA1 deficiency is restricted to cells of neuronal lineage, i.e., neurons and macroglia. Results The 10 most up-regulated genes in the ventral posteromedial/posterolateral region of the thalamus were inflammatory genes, with the gene expression signature significantly enriched in interferon signaling genes. Interferon β levels were elevated in neurons, and interferon-stimulated genes were elevated mainly in microglia. Interferon signaling pathways were elevated to a small extent in the brain of another lysosomal storage disease mouse model, Krabbe disease, but not in Niemann-Pick C or Sandhoff mouse brain. Ablation of the type I interferon receptor attenuated neuroinflammation but had no effect on GD mouse viability. Conclusions Our results imply that the type I interferon response is involved in the development of nGD pathology, and possibly in other lysosomal storage diseases in which simple glycosphingolipids accumulate, and support the notion that interferon signaling pathways play a vital role in the sterile inflammation that often occurs during chronic neurodegenerative diseases in which neuroinflammation is present.